Biocompatible and biodegradable fibrinogen microspheres for tumor-targeted doxorubicin delivery - Joo JY (Dove Medical Press, 2015)
Jae Yeon Joo, GilYong Park, SeongSoo A An Department of Bionano Technology, Gachon Medical Research Institute, Gachon University, Seongnam-si, Republic of Korea Abstract: In the development of effective drug delivery carriers, many researchers have focused on the usage of nontoxic and biocompatible materials and surface modification with targeting molecules for tumor-specific drug delivery. Fibrinogen (Fbg), an abundant glycoprotein in plasma, could be a potential candidate for developing drug carriers because of its biocompatibility and tumor-targeting property via arginine–glycine–aspartate (RGD) peptide sequences. Doxorubicin (DOX), a chemotherapeutic agent, was covalently conjugated to Fbg, and the microspheres were prepared. Acid-labile and non-cleavable linkers were used for the conjugation of DOX to Fbg, resulting in an acid-triggered drug release under a mild acidic condition and a slow-controlled drug release, respectively. In vitro cytotoxicity tests confirmed low cytotoxicity in normal cells and high antitumor effect toward cancer cells. In addition, it was discovered that a longer linker could make the binding of cells to Fbg drug carriers easier. Therefore, DOX–linker–Fbg microspheres could be a suitable drug carrier for safer and effective drug delivery. Keywords: biocompatibility, anti-cancer drug, micro-structure, cytotoxicity, bio-conjugation, tumor targeting